Conversational linguistic analysis of spoken discourse in ESL professional communication / Syamimi Turiman - Turiman, Syamimi (2018)
At the university level, various job interview training have been carried out to prepare future graduates for employment. However, the graduates' poor communication skills remain as one of the reasons for unemployment in Malaysia. Since job interviews are placed heavily on verbal exchanges between the interviewer and job candidate, the role that language plays in interaction is worth exploring. This study investigates the use of spoken metadiscourse in the Malaysian ESL job interviews to identify the types and frequencies of spoken metadiscourse employed; to examine the similarities and differences of metadiscourse across disciplines; and to explore how the metadiscourse features function in the said context. The data come from sixteen actual first-stage job interviews, whereby ten job interviews are from the technical discipline (i.e. science based profession) for the post of Plant Operation Engineer in a multinational company based in Malaysia; and six non-technical job interviews (i.e. social science and humanities job) for the post of English language lecturers in a public university in Malaysia. Corpus Linguistics and Corpus Analysis (CL/CA) methods were employed to analyse the textual and interpersonal metadiscourse in the corpus, both quantitatively and qualitatively. The quantitative findings revealed that the textual and interpersonal metadiscourse were used in the Malaysian ESL job interviews, but there were variations in the distribution and composition of metadiscourse in the two categories across disciplines. A notable finding was that the more detailed categories in the tentative metadiscourse framework proposed in the present study did prove useful in identifying similarities and differences in the use of metadiscourse across disciplines, and in explicating the metadiscourse subtypes which reflect power differences in job interview discourse. The qualitative analyses of metadiscourse which employed the CL/CA methods have revealed the specific functions and types of metadiscourse items occurring in the specific context throughout the job interview. CL/CA methods were found effective in investigating the use of metadiscourse in the Malaysian ESL job interviews. The study suggests that students at the tertiary level may benefit from explicit teaching of metadiscourse to enhance their communication skills. Training in the verbal aspects, specifically on metadiscourse in job interviews can be enhanced when learners are given the opportunity to reflect on their speech productions, so that they are better trained to gain control over their own language performance.